Intensi Ketua Rukun Tangga Mengendalikan Rokok: efek dari penyuluhan dengan leaflet dan video di Kabupaten Kutai Kartanegara - Rumhanik Yuli Utami; Rendra Widyatama; Fatwa Sari Tetra Dewi (Berita Kedokteran Masyarakat (BKM), 2016)
Neighborhood head intention in tobacco control: the effect of leaflet and video-based health education in Kutai Kartanegara DistrictPurposeThe purpose of this paper was to determine the effect of health education through counseling with leaflets and video in improving knowledge, attitude, and intention in smoking control by the heads of Kutai Kartanegara. MethodsA quasi-experimental study was conducted involving 68 heads of a neighborhood who were divided into an experimental group and a control group with equal people in each group in Kutai Kartanegara. Leaflets-based counseling was given to the experimental group, while video-based counseling was given to the control group. ResultsThe study found that there was an increase in knowledge, attitudes, and intentions in both groups. Results showed the health education using leaflets had better influence compared to the video method. ConclusionHealth education and counseling using leaflet and video media provided a significant influence in increasing knowledge, attitude and intention to control the smoking of the heads of the neighborhood. The method of health education through counseling with leaflets was more effective than video in improving the heads of neighborhood’s knowledge and intention of smoking control. The use of leaflet media and video playback in health education activities needs to be improved for better effectiveness of cigarette control.